Plant resistance to tomato yellow leaf curl virus is enhanced by Bacillus amyloliquefaciens Ba13 through modulation of RNA interference - Guo, Qiao; Sun, Yifan; Ji, Chenglong; Kong, Zirong; Liu, Zhe; Li, Yulong; Li, Yunzhou; Lai, Hangxian (Frontiers in Microbiology, 2023)
Tomato yellow leaf curl virus (TYLCV), which is a typical member of the genus Begomovirus, causes severe crop yield losses worldwide. RNA interference (RNAi) is an important antiviral defense mechanism in plants, but whether plant beneficial microbes used as biocontrol agents would modulate RNAi in defense against TYLCV remains unclear. Here, we employed whole-transcriptome, bisulfite, and small RNA sequencing to decipher the possible role of Bacillus amyloliquefaciens Ba13 as a bacterial biocontrol agent against TYLCV in RNAi modulation. Potted tomato plants were exposed to whiteflies for natural viral infection 14 days after bacterial inoculation. Compared with non-inoculated controls, the abundance of TYLCV gene in the leaves of inoculated plants decreased by 70.1% at 28 days post-infection, which mirrored the pattern observed for plant disease index. The expression of the ARGONAUTE family genes (e.g., AGO3, AGO4, AGO5, AGO7) involved in antiviral defense markedly increased by 2.44-6.73-fold following bacterial inoculation. The methylation level at CpG site 228 (in the open reading frame region of the RNA interference suppressing gene AV2) and site 461 (in the open reading frame regions of AV1 and AV2) was 183.1% and 63.0% higher in inoculated plants than in non-inoculated controls, respectively. The abundances of 10 small interfering RNAs matched to the TYLCV genome were all reduced in inoculated plants, accompanied by enhancement of photosystem and auxin response pathways. The results indicate that the application of B. amyloliquefaciens Ba13 enhances plant resistance to TYLCV through RNAi modulation by upregulating RNAirelated gene expression and enhancing viral genome methylation.